KONSEP BIOPHILIC ARCHITECTURE SEBAGAI PENDEKATAN PADA AL-QUR’AN CENTER DI GORONTALO - Nurmuhammad, Andi Annisa; Heryati, Heryati; Pratiwi, Niniek (Universitas Negeri Gorontalo, 2024)
Gorontalo regency is a city that possess a majority of Muslim population with a percentage of 98%. However, as times and technology have changed, many Muslims in Gorontalo have started to be influenced by foreign cultures that diverge greatly from Islamic teachings. The Gorontalo Muslim community in the globalization era must also face even more difficult challenges due to the intrussion of a culture of hedonizm, materializm and secularizm into human life. Thus, in order to meet this challenge, The Gorontalo Muslim community must increase their knowledge of their religion, specifically by reading the Qur’an and it also hoped that they will be able to resolve the widespread spiritual crisis that is presently plaguing them. For this reason, a forum is required that can emerge and revive the role of the Qur’an as a guideline for Muslim life, namely by building an Al-Qur’an Center in Gorontalo which prepares all facilities for Islamic activities based on the Qur’an and Hadith.The method used in the design and planning of Al-Qur’an Center is data collection, which is the first step to collect factual issues that become the background of the title selection then obtain data through observation, which is by collecting data directly from the research site, interview method and literature study method, namely studying, understanding, literatureand searching for sources related to the research object. The design of Al-Qur’an Center is anticipated to be the best effort to overcome the current spiritual crisis in Gorontalo. By emphasizing the concept of Biophilic Architecture, this design will foster a positive relationship between humans and nature with Architecture, this design will foster a positive relationship between humans and nature with architecture. Biophilic design seeks to produce a space that can participate in improving the physical and mental well-being of human life.